S77 Transcriptomic studies reveal monocyte-related genes as major contributor to disease activity in pulmonary sarcoidosis. (15th November 2017) - Kendrick, Y; Crawshaw, A; Lockstone, H; Giannoulatou, E; Argoud, K; Taylor, S; Ho, LP
Abstract : Despite major advances in characterising the disease pathogenesis of sarcoidosis, it is still unclear which immune pathway is the main contributor to disease activity. The most effective treatment, corticosteroids, has a high adverse effect burden so there is a need to define more specific therapeutic agents with less side effects. In addition, for some patients with progressive active disease, corticosteroids are often unhelpful; therefore better understanding of the mechanisms of disease is needed for development new drugs. This study examines the potential immune processes involved in disease activity in sarcoidosis using gene expression profiling of peripheral blood mononuclear cells (PBMCs) (n=29) and bronchoalveolar lavage cells (BALCs) (n=12). Patients with well-defined pulmonary sarcoidosis and secure tissue-supported diagnosis were recruited from the Oxford Sarcoidosis Service during a defined 2 year period. Patients were not on treatment at the point of sampling. A CTAS 1 -validated chest radiograph-blood disease activity score comprising lymphocyte, ACE and IgG levels (SCAS, scores from 0 to 12 reflecting low to high activity) was used to measure activity at the point of sampling. Gene expression profiles were derived from PBMC and BALCs using the Illumina HT-12 v4 expression chip. All RNA had a RIN≥8. We found a significant positive correlation between the 'immune response' gene set and SCAS for BALCs, by GSEA and Metacore functional analyses. Within this gene set, a transcriptional signature related to monocyte activity and function was shown to be the most significant gene network with an unexpected downregulation of TGFb receptor signalling pathway in low activity BALCs. In PBMCs and BALCs, the two IFN-g-inducible, monocyte-produced genes CXCL-9 and CXCL-10 were the soluble factors that most correlated with increasing activity (r≥0.5 by Spearman Correlation). In an independent cohort, SCAS levels were examined against CD14 hi classical monocyte levels (n=40, same inclusion criteria). This showed a marked correlation between monocyte frequency and level of activity as measured by SCAS (r=0.67; p<0.001; Spearman Rank correlation). These Results implicate monocytes as a major contributor to disease activity in sarcoidosis and propose monocyte pathways as potential specific targets for new therapeutics in sarcoidosis. Reference: 1. Benamore R, Kendrick Y, et al . Thorax 2017.